Electra : a tragedy / as translated from Sophocles ; with notes, by Mr. Theobald. Distinguishing also the variations of the theatre as performed at the Theatre-Royal in Drury-Lane. Regulated from the prompt-book ... by Mr. Hopkins, prompter. - Sophocles. (Tufts University. Tisch Library., 2015)
1 online resource (61, [3] pages, plate); At head of title page: 'Bell's edition'.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.